Anglos and Mexicans in the making of Texas, 1836-1986 - Montejano, David, 1948- (ACLS Humanities E-Book (Series), 1987)
A reconstruction of Mexican-Anglo relations in Texas from 1836-1986, with a focus on a 200-mile-wide strip paralleling the Mexican border from Brownsville to El Paso.